2006
DOI: 10.1182/blood-2005-03-1087
|View full text |Cite
|
Sign up to set email alerts
|

Severe secondary deficiency of von Willebrand factor–cleaving protease (ADAMTS13) in patients with sepsis-induced disseminated intravascular coagulation: its correlation with development of renal failure

Abstract: Deficiency of ADAMTS13 is found in patients with thrombotic thrombocytopenic purpura (TTP), and the genetic defects in the ADAMTS13 gene or the autoantibody against ADAMTS13 is thought to be responsible for the development of TTP. The clinical correlation and mechanisms of secondary ADAMTS13 deficiency in other disease states were investigated. In addition to TTP, ADAMTS13 levels were severely decreased in patients with sepsis-induced disseminated intravascular coagulation (DIC). The incidence of acute renal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
292
7
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(328 citation statements)
references
References 26 publications
(47 reference statements)
19
292
7
10
Order By: Relevance
“…A previous study (13) demonstrated that deficiency of ADAMTS13-associated inflammation promotes UL-VWFM the formation and severe, secondary ADAMTS13 deficiency can be associated with sepsis-induced DIC and may contribute to renal failure development (28), supporting the authors' data and hypothesis.…”
Section: Discussionsupporting
confidence: 69%
“…A previous study (13) demonstrated that deficiency of ADAMTS13-associated inflammation promotes UL-VWFM the formation and severe, secondary ADAMTS13 deficiency can be associated with sepsis-induced DIC and may contribute to renal failure development (28), supporting the authors' data and hypothesis.…”
Section: Discussionsupporting
confidence: 69%
“…The incidence of acute renal failure in patients with decreased ADAMTS13 levels was 41.2%. Decrease of the protein was due to a combination of increased cleavage together with a decreased synthesis of new ADAMTS 13 in the liver (Furlan and Lammle 2001;Mimuro et al 2008;Ono et al 2006). …”
Section: Von Willebrand Factor and Adamts13mentioning
confidence: 99%
“…Some studies have reported that ADAMTS13 is also decreased in conditions such as sepsis, disseminated intravascular coagulopathy and liver diseases, occasionally to very low levels [48][49][50]. However, these observations remain controversial [51;52], and the significance of decreased ADAMTS13 levels remains uncertain if they are not accompanied by evidence of decreased VWF proteolysis.…”
Section: Severe Adamts13 Deficiency Cause Thrombotic Thrombocytopenicmentioning
confidence: 99%